Older adults who move to independent living units: A regional Australian study. (10th May 2019) - Horstmanshof, Louise; Garbutt, Rob; Brownie, Sonya
Abstract: Objective: The purpose of this study was to ask older adults in a regional area of Australia how they made the decision to move into an independent living unit (ILU) within a three‐tier residential complex that provides varying services and care to older adults. Method: Focus groups were used to enable the gathering of rich data and to enable the voices of older adults. A deductive qualitative analysis (Gilgun, Qualitative research in social work, 2nd ed., pp. 107–135, 2013) was deployed using the factors for a successful later‐life transition to an aged‐care facility identified in the researchers' earlier systematic review. Results: Feelings of autonomy and control over the decision to move were important to all respondents. Any sense of loss of day‐to‐day autonomy, privacy and purpose, was compensated for by increased feelings of safety and security. Selected items brought from the old home to the new were a significant source of comfort. Conclusions: This study provides the views and experiences of 19 older adults from regional Australia about moving into ILUs in a three‐tier complex. The values and missions of the complex were important in the relocation decision‐making. Further, if the choice is between living near friends or family, participants recommended choosing friends. The strategic choice of an ILU in a three‐tier complex was seen as providing appropriate care into an unknown future. This study highlights the importance for older adults, their families and health‐care professionals of making timely relocation decisions and the importance for older adults to retain autonomy and control over the relocation decision.